OPTIMIZATION OF DESIGN PARAMETERS FOR DEPTH ELECTROMAGNETIC SPEED SENSOR - Avanesov, Y L; Bukanova, A N; Voronov, A S; Evstifeev, M I (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2018)
Subject of Research.Design features of a deep water electromagnetic speed sensor are considered. The principle of its operation is described; a finite-element model is developed. The design solutions that improve the performance of the induction sensor are shown. The design parameters are optimized by the criterion of strength increase. Method. The study was performed using the finite element method in the ANSYS Workbench software. The calculations were performed in the Static Structural module with account for the distributed load simulating external hydrostatic pressure. To determine the effect of mechanical stresses on the design parameters a parametric model is used. The parameters in this model are ranged within the prescribed limits. At calculations all materials are taken to be isotropic. Main Results. Calculating results of induction sensor stress-strain state under the impact of external hydrostatic load were obtained by the method of finite element analysis. The effect of the sensor case material, its thickness and geometry, on the maximum stresses arising in the structure is studied. Recommendations on the choice of design parameters are given for increasing the strength of the induction sensor confirmed by computer simulation. Practical Relevance. The results obtained can be applied in modernization, design and construction of new electromagnetic speed sensors operating at high hydrostatic pressures.